2020
DOI: 10.31703/gesr.2020(v-ii).06
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Mobile Application on Learning Among Teachers Based on Technology Acceptance Model (TAM)

Abstract: Mobile learning and digital communication are known as the most advanced tool to get competitive edge over other in the current globalized world. The current research study tries to investigate the adaptation of mobile acceptance model among teachers in District Bannu. Researchers try to investigate the teachers' attitude, performance and learning capabilities with the usage of mobile technology. Target population of the study is 2000 newly recruited teachers, while sample size of 220 was drawn based on the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Several studies [30][31][32] have been carried out to investigate the elements that impact consumers' adoption of M-learning. According to [33], academics did not take a thorough enough strategy while examining the attitudes of the pupils in a high school instructional situation.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Several studies [30][31][32] have been carried out to investigate the elements that impact consumers' adoption of M-learning. According to [33], academics did not take a thorough enough strategy while examining the attitudes of the pupils in a high school instructional situation.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Students and instructors have been shown to benefit from M-learning, with improved face-to-face and remote student involvement [8]. Several studies have investigated the impact of M-learning on consumer usage [9,10], and many students and instructors have been the focus of M-learning [11,12]. Although mobile devices are one of the main tools associated with learning, being entertained, and teaching [13], there are still very few guidelines on the sustainability and transfer of mobile learning initiatives [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile App Usage (MAU): After a deep analysis of the existent literature, it can be highlighted that the impact of the mobile apps usage has directly influenced the TAM and that mobile app usage has had a positive impact on teacher performance and learning capabilities [31]. In this other study [32], it was observed that the perceived ease of use and perceived usefulness of mobile apps positively affected hotel consumers' experiences.…”
mentioning
confidence: 92%